2005
DOI: 10.1590/s0101-31222005000200001
|View full text |Cite
|
Sign up to set email alerts
|

Germinação e morfologia de sementes e de plântulas de hortelã-do-campo Hyptis cana Pohl. (Lamiaceae)

Abstract: RESUMO -Estudos de morfologia de sementes e de plântulas de espécies nativas do cerrado durante a germinação fornecem informações fundamentais para sua identificação, para interpretação dos testes de germinação em laboratório e para estudos sobre seu ciclo biológico e regeneração natural. O objetivo deste trabalho foi descrever características externas e internas da semente, além de detalhar e ilustrar o processo germinativo e a morfologia das plântulas de hortelã-do-campo. O teste de germinação foi conduzido … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
1
0
1
Order By: Relevance
“…For all species, the apical tips have a rounded shape, except in H. suaveolens, which has seeds with a median longitudinal ridge, starting near the hilum and extending to the apex of the seed with retuse boundary (Figure 1). The hilum is located in the proximal end at the base of the seed, whitish color, with 'V' aspect on the ventral side, being more pronounced at H. macrostachys and linear in H. Data involving germination and morphology of field-mint (Hyptis cana) showed dark brown seed coat, opaque, rough and whitish hilum (VUADEN et al, 2005), these characteristics being similar to those found in medicinal and aromatic species endemic in the semiarid region of northeastern Brazil.…”
Section: Resultssupporting
confidence: 52%
“…For all species, the apical tips have a rounded shape, except in H. suaveolens, which has seeds with a median longitudinal ridge, starting near the hilum and extending to the apex of the seed with retuse boundary (Figure 1). The hilum is located in the proximal end at the base of the seed, whitish color, with 'V' aspect on the ventral side, being more pronounced at H. macrostachys and linear in H. Data involving germination and morphology of field-mint (Hyptis cana) showed dark brown seed coat, opaque, rough and whitish hilum (VUADEN et al, 2005), these characteristics being similar to those found in medicinal and aromatic species endemic in the semiarid region of northeastern Brazil.…”
Section: Resultssupporting
confidence: 52%
“…The new leaves are light green on the upper side and a lighter, grayishgreen shade on the underside; the chalice is grayishgreen with shades of dark purple; and the corolla is purple, with an 8-10 mm long tube, and a 4 mm long, slightly rimmed nucleus (Epling, 1949). The seeds have rough, dark brown, opaque tegument and whitish basal hilum (Vuaden et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As sementes de H. canum possuem tegumento castanhoescuro, opaco, rugoso e hilo basal e esbranquiçado. A germinação é fanerocotiledonar e a emergência é epígea (Vuaden et al, 2005).…”
Section: Introductionunclassified